Post-translational processing of the low density lipoprotein receptor - Ozinsky, Adrian (Division of Medical Biochemistry and Structural Biology, 2017)
The low density lipoprotein (LDL) receptor is a transmembrane glycoprotein that mediates the uptake of plasma LDL and thereby provides cholesterol to cells. During its synthesis in the endoplasmic reticulum, the LDL receptor folds and forms disulfide bonds in multiple cysteine-rich repeats. N- and 0-linked oligosaccharide chains are added in the endoplasmic reticulum and processed during passage through the Golgi apparatus, en route to the cell surface. The aim of this thesis was to study the influence of post-translational events on the synthesis of the LDL receptor. Experiments addressed: 1) the necessity of the compartmental organisation of the secretory pathway for the glycosylation of the LDL receptor; 2) the requirements for the formation of disulfide bonds; 3) the role for the chaperone, calnexin, in the folding of the LDL receptor; and 4) the manner in which folding was disrupted by mutations. Experiments were performed in cultured cells that were incubated with [³⁵S]methionine. Biosynthetically-labelled LDL receptor was immunoprecipitated and was analysed by SOS polyacrylamide gel electrophoresis.